2022
DOI: 10.1177/08862605221111411
|View full text |Cite
|
Sign up to set email alerts
|

Sexual, Physical, and Emotional Maltreatment in Childhood Are Differentially Associated With Sexual and Physical Revictimization in Adulthood

Abstract: Childhood maltreatment increases risk for sexual and physical revictimization in adulthood. The goal of the current study was to examine whether this risk is associated with specific maltreatment types (i.e., sexual vs. physical vs. emotional maltreatment vs. neglect) and perpetrators (i.e., mother vs. father). Participants included 720 adult women from North America and the United Kingdom, recruited through the online platform Prolific Academic. The severity of childhood maltreatment and adult physical and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…The study found partial support for Freyd's betrayal trauma theory. 38 Consistent with prior research, 39 trans persons who experienced parental physical maltreatment were more likely to report revictimization in adulthood. When different types of childhood victimization were modeled simultaneously, emotional maltreatment (bullying), sexual maltreatment, and parental physical victimization were significantly associated with revictimization in adulthood.…”
Section: Discussionsupporting
confidence: 76%
“…The study found partial support for Freyd's betrayal trauma theory. 38 Consistent with prior research, 39 trans persons who experienced parental physical maltreatment were more likely to report revictimization in adulthood. When different types of childhood victimization were modeled simultaneously, emotional maltreatment (bullying), sexual maltreatment, and parental physical victimization were significantly associated with revictimization in adulthood.…”
Section: Discussionsupporting
confidence: 76%
“…Particularly the childhood abuse group was small, as respondents who had experienced trauma both in childhood and adulthood were excluded from the analysis. The fact that more than half of the victims experienced abuse both in childhood and in adulthood is consistent with the phenomenon of revictimization: childhood abuse increases the risk of revictimization in adulthood 23 …”
Section: Discussionsupporting
confidence: 62%
“…The fact that more than half of the victims experienced abuse both in childhood and in adulthood is consistent with the phenomenon of revictimization: childhood abuse increases the risk of revictimization in adulthood. 23…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The Stress and Developmental symposium discussed the feasibility of pivoting stress research in children to remote platforms and the role of parental care and childhood adversity on the regulation of stress-sensitive systems [27][28][29][30]. Presenters showed that stress reactivity in young children is not only moderated by the child's mental health risk status but may also be buffered by parental presence during stress induction [29].…”
Section: Symposia Highlightsmentioning
confidence: 99%
“…Although current findings are inconclusive [28], parental training interventions to enhance nurturing care have been proposed to help regulate stress-sensitive systems and to foster the wellbeing of the developing child. A sex and gender lens was also incorporated into this symposium, showing that early childhood maltreatment is robustly associated with revictimization among women; however, a more nuanced exploration of the type of maltreatment, the perpetrator (i.e., maternal or paternal), and sexual identity (monosexual vs. plurisexual) is integral to understanding how early childhood maltreatment may result in revictimization later in adulthood [30].…”
Section: Symposia Highlightsmentioning
confidence: 99%